2021
DOI: 10.3390/ijms22168431
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Anti-Allergic Effects of Saponarin and Its Impact on Signaling Pathways of RAW 264.7, RBL-2H3, and HaCaT Cells

Abstract: Saponarin{5-hydroxy-2-(4-hydroxyphenyl)-6-[3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]-7-[3,4,5-trihydroxy-6-(hydroxymethyl)oxan-2-yl]oxychromen-4-one}, a flavone found in young green barley leaves, is known to possess antioxidant, antidiabetic, and hepatoprotective effects. In the present study, the anti-inflammatory, anti-allergic, and skin-protective effects of saponarin were investigated to evaluate its usefulness as a functional ingredient in cosmetics. In lipopolysaccharide-induced RAW264.7 (murine macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 93 publications
(142 reference statements)
0
15
0
Order By: Relevance
“…In our study, we found significantly increased amounts of saponarin, prunetin, 3- O -acetylpinobanksin, methylhesperidin, and other flavonoids in BsR than in BcR. Saponarin, which is the sole flavonoid present in barley sprout leaves ( Kim et al, 2022 ), possesses potent antioxidant ( Kamiyama and Shibamoto, 2012 ) and hepatoprotective activities ( Simeonova et al, 2013 ), and can be potentially used to prevent and relieve immune-related skin diseases ( Min et al, 2021 ). Prunetin has anti-inflammatory effects ( Abusaliya et al, 2022 ), prevents hepatocellular carcinogenesis by improving functions of the liver ( Li G. et al, 2022 ), and suppresses high-fat diet (HFD)-induced adipogenesis in the liver tissues of mice by regulating gene expression in liver tissue ( Ahn et al, 2013 ).…”
Section: Discussionmentioning
confidence: 85%
“…In our study, we found significantly increased amounts of saponarin, prunetin, 3- O -acetylpinobanksin, methylhesperidin, and other flavonoids in BsR than in BcR. Saponarin, which is the sole flavonoid present in barley sprout leaves ( Kim et al, 2022 ), possesses potent antioxidant ( Kamiyama and Shibamoto, 2012 ) and hepatoprotective activities ( Simeonova et al, 2013 ), and can be potentially used to prevent and relieve immune-related skin diseases ( Min et al, 2021 ). Prunetin has anti-inflammatory effects ( Abusaliya et al, 2022 ), prevents hepatocellular carcinogenesis by improving functions of the liver ( Li G. et al, 2022 ), and suppresses high-fat diet (HFD)-induced adipogenesis in the liver tissues of mice by regulating gene expression in liver tissue ( Ahn et al, 2013 ).…”
Section: Discussionmentioning
confidence: 85%
“…The β-hexosaminidase release was chosen as the index of degranulation. 20,21 As shown in Fig. 9B, the β-hexosaminidase release was inhibited after adding Dap., and the inhibitory effects were expressed dose-dependently by Dap.…”
Section: Effects Of Dap On Degranulation From Antigen-stimulated Rbl-...mentioning
confidence: 81%
“…The signaling cascade activation regulates the degranulation and production of allergic and inflammatory cytokines. 21 The inhibitory effect on the degranulation of antigen-stimulated RBL-2H3 cells was investigated. The β-hexosaminidase release was determined as an index of degranulation.…”
Section: Discussionmentioning
confidence: 99%
“…Although flavonoids such as apigenin and luteolin have shown to be cytotoxic, their glycosides were much less so [23]. Previously, the phenolic extracts from D. sativus containing saponarin, isoorientin and isovitexin have been proven to reveal antioxidant activities [17], and moreover, saponarin has been recently shown to possess anti-inflammatory and anti-allergic effects [24]. The other main constituents were chlorogenic acid (NP8) and dichlorogenic acid isomers (NP7).…”
Section: Resultsmentioning
confidence: 99%